2009
DOI: 10.1371/journal.pone.0007681
|View full text |Cite
|
Sign up to set email alerts
|

Effect before Cause: Supramodal Recalibration of Sensorimotor Timing

Abstract: BackgroundOur motor actions normally generate sensory events, but how do we know which events were self generated and which have external causes? Here we use temporal adaptation to investigate the processing stage and generality of our sensorimotor timing estimates.Methodology/Principal FindingsAdaptation to artificially-induced delays between action and event can produce a startling percept—upon removal of the delay it feels as if the sensory event precedes its causative action. This temporal recalibration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
138
6
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(166 citation statements)
references
References 43 publications
21
138
6
1
Order By: Relevance
“…PSS was shifted approximately 20% of the trained discrepancy in both directions. This is consistent with our earlier results (Rohde & Ernst, 2013), where participants shifted 20-25% of the trained discrepancy but less than in other studies, where PSS-shifts of the order of 30-44% are reported for visuomotor delay adaptation (Stetson et al, 2006;Heron et al, 2009;Sugano et al, 2010).…”
Section: Temporal Order Judgmentssupporting
confidence: 93%
See 4 more Smart Citations
“…PSS was shifted approximately 20% of the trained discrepancy in both directions. This is consistent with our earlier results (Rohde & Ernst, 2013), where participants shifted 20-25% of the trained discrepancy but less than in other studies, where PSS-shifts of the order of 30-44% are reported for visuomotor delay adaptation (Stetson et al, 2006;Heron et al, 2009;Sugano et al, 2010).…”
Section: Temporal Order Judgmentssupporting
confidence: 93%
“…While this result supports our conclusion that ML recalibration is biased towards a shift of the µ M criterion, it also suggests a small shift of the µ V criterion. In a similar paradigm, Heron et al (2009) only report the midpoint of the distribution (PSS), but graphical depiction of results from an example participant suggest a result similar to that reported by . However, both Heron et al (2009) and measure SJ responses at only five SOAs from the ML-side and use a Gaussian function to approximate the responses.…”
Section: Visuomotor Vs Visuo-auditory Temporal Recalibrationsupporting
confidence: 62%
See 3 more Smart Citations